A Short History of the Butrint Foundation's Conservation Programme at Butrint, Albania: 1994–2012. (November 2013) - Hodges, Richard; Paterlini, Anna
<x content-type="archive" xml:space="preserve">Abstract</x> This short history describes the work of the Butrint Foundation's operations in the area of conservation over the course of nearly twenty years. It pays particular attention to describing the relations with the Albanian authorities, especially the Institute of Monuments, and reviews how conservation of this UNESCO World Heritage Site proceeded during the unstable decade following the end of communism in 1991/2. The history also sets out the detailed work undertaken each year by the Foundation until it handed over operations to Albanian conservators and their support staff that the Foundation had helped to train.